1992
DOI: 10.1161/01.atv.12.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes may amplify their recruitment into inflammatory lesions by inducing monocyte chemotactic protein.

Abstract: By Northern analysis, freshly isolated monocytes contained no detectable mRNA for monocyte chemotactic protein-1 (MCP-1). However, after 4 hours of incubation at 37°C, MCP-1 mRNA was clearly induced in the monocytes and was found to be highly dependent and directly proportional to the monocyte density. The level of MCP-1 mRNA continued to increase, reaching a peak after 22 hours of incubation. After 3 days in culture, MCP-1 mRNA levels had declined substantially and after 8 days were undetectable in the monocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 27 publications
1
28
0
1
Order By: Relevance
“…Studying the arteries of human fetuses, they found that LDL was present and was oxidized before the entry of monocytes and that monocyte entry occurred at sites of oxidized LDL accumulation, strongly suggesting that LDL oxidation is a cause of monocyte entry and not just a by-product of monocyte metabolism (19). Berliner and colleagues (20)(21)(22)(23)(24)(25)(26) reported that mildly oxidized LDL, which was still recognized by the LDL receptor, stimulated human aortic endothelial cells to bind monocytes but not neutrophils and caused artery wall cells to produce the potent monocyte chemoattractant monocyte chemoattractant protein-1 and the differentiation factor monocyte colony stimulating factory. Subsequently, it was found that the biological activity of this minimally modified LDL (MM-LDL) was attributable to the oxidation of LDL phospholipids, which contain arachidonic acid in the sn -2 position (27)(28)(29)(30)(31)(32)(33)(34).…”
Section: What Causes Monocytes To Enter the Artery Wall In The First mentioning
confidence: 99%
“…Studying the arteries of human fetuses, they found that LDL was present and was oxidized before the entry of monocytes and that monocyte entry occurred at sites of oxidized LDL accumulation, strongly suggesting that LDL oxidation is a cause of monocyte entry and not just a by-product of monocyte metabolism (19). Berliner and colleagues (20)(21)(22)(23)(24)(25)(26) reported that mildly oxidized LDL, which was still recognized by the LDL receptor, stimulated human aortic endothelial cells to bind monocytes but not neutrophils and caused artery wall cells to produce the potent monocyte chemoattractant monocyte chemoattractant protein-1 and the differentiation factor monocyte colony stimulating factory. Subsequently, it was found that the biological activity of this minimally modified LDL (MM-LDL) was attributable to the oxidation of LDL phospholipids, which contain arachidonic acid in the sn -2 position (27)(28)(29)(30)(31)(32)(33)(34).…”
Section: What Causes Monocytes To Enter the Artery Wall In The First mentioning
confidence: 99%
“…[17][18][19][20] Monocytes possess the capacity to modulate immune responses by secreting chemokines and processing/presenting exogenous and "self" antigens. [21][22][23] Functional responses of monocytes (and other cells of the innate immune system) are also governed, in part, via germline-encoded pattern-recognition receptors, evolved to detect specific molecular motifs. 24 The present study investigates human monocyte responses to a major commercial isocyanate, hexamethylene diisocyanate (HDI), primarily used in protective spray coatings (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…8,17 MCP-1 is an attractor and activator of monocytes. 12 Both MCP-1 and PDGF are currently thought to be intimately involved in the pathogenesis of atherosclerosis. 8,9,18 It is currently unknown whether human gene expression for PDGF-A and PDGF-B can be reduced by other dietary unsaturated fatty acids, such as -6 or -9 fatty acids, or is reduced solely and specifically by -3 fatty acids.…”
mentioning
confidence: 99%